2018
DOI: 10.1007/s13224-017-1061-9
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphism-Based Noninvasive Prenatal Testing: Experience in India

Abstract: He has an experience of 51 years in the field of genetics and added valuable contribution in the field of pediatric genetics and community health in India. He handled approximately 2000 cases with expertise in Fetal Medicine and Reproductive Genetics. Current areas of interest and/or active clinical practices: Management of fetal medicine and reproductive genetics; Dysmorphology; Genetic counseling and prenatal diagnosis using molecular, cytogenetic and biochemical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…A study of NIPT's effectiveness conducted in India with 516 pregnant people at an intermediate (1:1,000 to 1:250) to high (greater than 1:250) chance of T21 showed a lower positive predictive value for T21 compared with other studies (168). However, the overall positive predictive value for T21, T18, T13, and monosomy X was similar to that of other studies.…”
Section: Indiasupporting
confidence: 65%
“…A study of NIPT's effectiveness conducted in India with 516 pregnant people at an intermediate (1:1,000 to 1:250) to high (greater than 1:250) chance of T21 showed a lower positive predictive value for T21 compared with other studies (168). However, the overall positive predictive value for T21, T18, T13, and monosomy X was similar to that of other studies.…”
Section: Indiasupporting
confidence: 65%
“…FCA rates were typical of the distribution in an unselected population [ 2 , 18 , 19 ]. Comparisons of the groups with and without outcome data showed a similar distribution except for a slightly higher high-risk rate in the no-outcome record group (Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2.3%) [22]. We found that the median fetal fraction in the group of no-call cases was more than three times lower in comparison with other groups.…”
Section: Discussionmentioning
confidence: 46%
“…Previous publications showed that PPV was 97.4% for trisomy 21 and 88.9% for trisomy 18 [21]. However, an Indian study estimated PPV of trisomy 21 and sex chromosome abnormalities XXX, XXY (80% and 50%, respectively), which was much lower compared with our results, but PPV of trisomy 18 was identical to the findings obtained from our research (100%) [22]. An important issue is that any high-risk score in NIPT should be confirmed by invasive prenatal diagnosis before any decisions about pregnancy.…”
Section: Discussionmentioning
confidence: 88%